Complete genome sequence of a new enamovirus from Argentina infecting alfalfa plants showing dwarfism symptoms - Bejerman, Nicolás; Giolitti, Fabián; Trucco, Verónica; de Breuil, Soledad; Dietzgen, Ralf G.; Lenardon, Sergio (Archives of virology, 2016)
Alfalfa dwarf disease, probably caused by synergistic interactions of mixed virus infections, is a major and emergent disease that threatens alfalfa production in Argentina. Deep sequencing of diseased alfalfa plant samples from the central region of Argentina resulted in the identification of a new virus genome resembling enamoviruses in sequence and genome structure. Phylogenetic analysis suggests that it is a new member of the genus Enamovirus , family Luteoviridae . The virus is tentatively named “alfalfa enamovirus 1” (AEV-1). The availability of the AEV-1 genome sequence will make it possible to assess the genetic variability of this virus and to construct an infectious clone to investigate its role in alfalfa dwarfism disease.